Comprehensive characterization of TSV etching performance with phase‐contrast X‐ray microtomography. (27th May 2020) - Li, Ke; Deng, Biao; Zhang, Haipeng; Yu, Fucheng; Xue, Yanling; Xie, Changqing; Ye, Tianchun; Xiao, Tiqiao
Abstract : A complete method of comprehensive and quantitative evaluation of through‐silicon via reliability using a highly sensitive phase‐contrast X‐ray microtomography was established. Quantitative characterizations include 3D local morphology and overall consistency of statistics. Abstract : Comprehensive evaluation of through‐silicon via (TSV) reliability often requires deterministic and 3D descriptions of local morphological and statistical features of via formation with the Bosch process. Here, a highly sensitive phase‐contrast X‐ray microtomography approach is presented based on recorrection of abnormal projections, which provides comprehensive and quantitative characterization of TSV etching performance. The key idea is to replace the abnormal projections at specific angles in principles of linear interpolation of neighboring projections, and to distinguish the interface between silicon and air by using phase‐retrieval algorithms. It is demonstrated that such a scheme achieves high accuracy in obtaining the etch profile based on the 3D microstructure of the vias, including diameter, bottom curvature radius, depth and sidewall angle. More importantly, the 3D profile error of the via sidewall and the consistency of parameters among all the vias are achieved and analyzed statistically. The datasets in the results and the 3D microstructure can be applied directly to a reference and model for further finite element analysis. This method is general and has potentially broad applications in 3D integrated circuits.